White matter alterations in adults with probable developmental coordination disorder: an MRI diffusion tensor imaging study. Issue 2 (18th January 2017) - Williams, Jacqueline; Kashuk, Saman R.; Wilson, Peter H.; Thorpe, Graham; Egan, Gary F.
Abstract : Movement skill difficulties in children [or developmental coordination disorder (DCD)] often persist into adulthood (in up to 70% of cases). The suggestion of white matter microstructure alterations in children with DCD raises the question of whether similar alterations are present in adults with probable DCD (pDCD). Twelve adults with pDCD and 11 adults without pDCD underwent diffusion tensor imaging. The results showed that the pDCD group had significantly lower fractional anisotropy in the corticospinal tract and superior longitudinal fasciculus and lower mean diffusivity in the internal capsule and inferior longitudinal fasciculus. This suggests reduced white matter integrity in parietofrontal and corticospinal tracts, with possible compensatory increases in white matter integrity along the visual ventral stream and front-occipital networks. These findings support recent neuroimaging studies in children with DCD and suggest persistent neurobiological alterations along white matter tracts that are known to support motor planning, cognition and their association.